2023
DOI: 10.3390/pathogens12020260
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pathogenic Leptospira kirschneri Serogroup Grippotyphosa in Water Voles (Arvicola terrestris) from Ruminant Pastures in Puy-de-Dôme, Central France

Abstract: Rodents are the primary reservoirs for pathogenic Leptospira species, which cause leptospirosis. Among the key potential carriers are water voles, whose population outbreaks can consequently pose a major threat to human and animal health. We studied the prevalence, prominence, and epidemiology of pathogenic Leptospira species in water voles in central France. First, 46 voles were captured, and DNA was extracted from kidney, lung, liver, blood, and urine and tested for the presence of Leptospira using three mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The 16S rRNA target showed a 36.7% improvement in the detection of low-level positive samples, especially for detecting a higher number of positive animals with Ct values above 30. This method should therefore be favored in the future [ 46 , 47 ]. At the opposite, several studies affirm that lipL32 has better specificity to detect all pathogenic Leptospira spp., because the lipL32 gene is present only in pathogenic species [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA target showed a 36.7% improvement in the detection of low-level positive samples, especially for detecting a higher number of positive animals with Ct values above 30. This method should therefore be favored in the future [ 46 , 47 ]. At the opposite, several studies affirm that lipL32 has better specificity to detect all pathogenic Leptospira spp., because the lipL32 gene is present only in pathogenic species [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of zoonotic disease in new localizations, as well as the sources of transmission between wild and domestic animals, is of great importance in terms of the epidemiological dimension. For many years, small ruminants had been considered as accidental hosts of leptospires, but several studies have shown that leptospiral infection in goats and sheep is common, and these species can also act as only maintenance hosts for serovars and carriers of leptospires eliminating the microorganisms on the environment for long time periods [ 44 ]. The maintenance hosts tend to be infected by serovars that colonize the kidneys and are shed in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…Wild rodents are the main reservoirs for pathogenic Leptospira species as serovar Grippotyphosa, which cause leptospirosis in sheep [ 50 ]. Transmission of Leptospira serovars requires a continuous enzootic circulation of the organism between animals, although with the possibility of introduction of new serovars from animal reservoirs, both wildlife and domestic animals [ 44 ]. According to Guedes et al [ 51 ], the microscopic agglutination test is a good serological technique for the detection of antibodies against Leptospira serovars, but cross-reactions and paradoxical reactions are frequently observed with MAT.…”
Section: Discussionmentioning
confidence: 99%
“…As described elsewhere, neither the seropositivity nor the titre levels predicted Leptospira infection (Harran et al, 2023). Thus, further work must be carried out -using bacterial cultivation and additional molecular tools -to determine whether Canicola's predominance is a specificity of Benin or a spurious result of MAT crossreactions.…”
Section: Idmentioning
confidence: 92%